Azithromycin-loaded liposomal hydrogel: a step forward for enhanced treatment of MRSA-related skin infections - Rukavina Zora; Jøraholmen May Wenche; Božić Dunja; Frankol Ivana; Gašparović Petra Golja; Škalko-Basnet Nataša; Klarić Maja Šegvić; Vanić Željka (Acta Pharmaceutica)
Azithromycin (AZT) encapsulated into various types of liposomes (AZT-liposomes) displayed pronounced in vitro activity against methicillin-resistant Staphylococcus aureus (MRSA) (1). The present study represents a follow-up to this previous work, attempting to further explore the anti-MRSA potential of AZT-liposomes when incorporated into chitosan hydrogel (CHG). Incorporation of AZT-liposomes into CHG (liposomal CHGs) was intended to ensure proper viscosity and texture properties of the formulation, modification of antibiotic release, and enhanced antibacterial activity, aiming to upgrade the therapeutical potential of AZT-liposomes in localized treatment of MRSA-related skin infections. Four different liposomal CHGs were evaluated and compared on the grounds of antibacterial activity against MRSA, AZT release profiles, cytotoxicity, as well as texture, and rheological properties. To our knowledge, this study is the first to investigate the potential of liposomal CHGs for the topical localized treatment of MRSA-related skin infections. CHG ensured proper viscoelastic and texture properties to achieve prolonged retention and prolonged release of AZT at the application site, which resulted in a boosted anti-MRSA effect of the entrapped AZT-liposomes. With respect to anti-MRSA activity and biocompatibility, formulation CATL-CHG (cationic liposomes in CHG) is considered to be the most promising formulation for the treatment of MRSA-related skin infections.